2016
DOI: 10.5978/islsm.16-or-24
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of retention of pit and fissure sealants placed with conventional acid etching and Er,Cr:YSGG laser etching: A randomised controlled trial

Abstract: Aim:The aim of this study was to compare the retention rates of sealant placed either with conventional acid etching or Er,Cr:YSGG laser pretreatment of enamel surface. Materials and methods: This is a prospective, single blind randomised controlled clinical trial enrolling 200 permanent first molars in 50 patients, aged 6-12 years for sealant placement. Study followed split mouth design where each side of the arch was randomly allocated to the two treatment group. Group A(Acid etch group): 37 % phosphoric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 25 publications
1
37
0
2
Order By: Relevance
“…The level of consistency found (kappa coefficient of agreement) between two reviewers performing the initial screening of records was high (κ value=0.93). After the full text examination, nine studies (10 publications [20][21][22][23][24][25][26][27][28][29] ) meeting the inclusion criteria were included (figure 1 and table 1), while the remaining 23 studies were excluded due to the reasons reported in the online supplemental appendix 2. The study carried out by Nammour et al was described in two publications.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The level of consistency found (kappa coefficient of agreement) between two reviewers performing the initial screening of records was high (κ value=0.93). After the full text examination, nine studies (10 publications [20][21][22][23][24][25][26][27][28][29] ) meeting the inclusion criteria were included (figure 1 and table 1), while the remaining 23 studies were excluded due to the reasons reported in the online supplemental appendix 2. The study carried out by Nammour et al was described in two publications.…”
Section: Resultsmentioning
confidence: 99%
“…The study carried out by Nammour et al was described in two publications. 25 26 All nine studies [20][21][22][23][24][25][26][27][28][29] were written in English.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations